Respon Pertumbuhan Miselia F2 pada Media PDA dan F3 pada Baglog Beberapa Nomor Isolat Harapan Jamur Merang (Volvariella volvaceae) FAPERTA UNSIKA secara In Vitro - Widya Pramudita; Ani Lestari; Devie Rienzani Supriadi (JURNAL AGROPLASMA, 2023)
Straw mushroom (Volvariella volvaceae) is a type of edible mushroom that is great demand because it has good nutrition and high economic value. In the cultivation of straw mushroom, pure culture is needed which is free from contamination and has superior genetic characteristics both in terms of quality and quantity, which will then produce superior straw mushroom seeds. Superior seeds are factors that affect the production and yield of straw mushroom. The purpose of this study was to obtain one hopeful isolate of the straw mushroom Faperta UNSIKA that gave the best mycelial growth in vitro. The research was conducted at the Laboratory of Biotechnology and Plant Breeding, Faculty of Agriculture, Singaperbangsa Karawang University, located in Puseurjaya Village, Telukjambe Timur District, Karawang Regency and start from December 2022 - February 2023. The research method used was experimental with a single factor Randomized Block Design (RBD). There are 7 treatments, namely A (White Elder), B (Semi Elder), C (FP016), D (FP018), E (FP019), F (FP020) and G (FP021). Each treatments was repeated 5 times. The effect of the treatment was analyzed by analysis of variance and if the F test at 5% level was significant, to find out the best treatment, proceed with the DMRT (Duncan Multiple Range Test) at the 5% level. The results showed that there was a significant effect of some numbers hopeful isolate straw mushroom Faperta UNSIKA on the growth of F2 mycelia on PDA media and F3 on baglog in vitro. Treatment A (White Elder) gave the highest yield on the growth diameter of F2 mycelia on PDA media of 6,40 cm with the highest growth rate of 1,91 cm/day and treatment E (FP019) gave the highest yield on the growth length of F3 mycelia baglog of 13,21 cm with the highest growth rate of 2,70 cm/day. Keywords: Isolate Faperta UNSIKA, Mycelia, Straw Mushroom